Comparative study of red blood cell morphology in peripheral smear and automated cell counter - Dr. Sunita C. Goyal; Dr. Nilay L. Shah; Dr. F.R. Shah; Dr. J.M.Shah (Tropical Journal of Pathology and Microbiology, 2019)
Background: Automated cell counters are a very important part of pathology laboratory for evaluation of complete blood count (CBC). They also provide RBC histograms to interpret differentmorphological variations of Red Blood Cells.These histograms and other parameters have been found veryuseful in diagnosing various hematological conditions and Red Blood Cell disorders if they are correctly interpreted.Examination of peripheral smears is still the gold standardfor diagnosing some of the RBC disorders which might not be diagnosed otherwise by automated cell counters. They play an important role in quality check of automated analyzers. Materials and Methods:In this prospective study we have taken 200 samples over a period of 6 months. We did comparative study between RBC histograms obtained by automated hematology analyzer and peripheral blood smears stained by field stain. We have discussed morphological variations of red blood cells and their characteristic changes in respective RBC histograms. Result:Out of 200 samples of RBC histogram interpretation, 138 cases showed correlation with peripheral smear findings while 62 cases showed discrepancies. Conclusion: Microscopic examination of peripheral blood smear still remains gold standard for diagnosis of various hematological conditions.